Development of a multiplex polymerase chain reaction assay for simultaneous identification of human enterovirus 71 and coxsackievirus A16. - Thao, Nguyen Thi Thanh; Ngoc, Nguyen Thi Kim; Tú, Phan Van; Thúy, Tr`an Thi; Cardosa, Mary Jane; McMinn, P.C; Phuektes, Patchara (Elsevier, 2010)
Human enterovirus 71 (HEV71) and coxsackievirus A16 (CVA16) are two major aetiological agents of hand, foot and mouth disease (HFMD) in children. Recently there have been several large outbreaks of HFMD in Vietnam and the Asia-Pacific region. In this study, a multiplex RT-PCR assay was developed in order to detect simultaneously HEV71, CVA16 and other human enteroviruses. Enterovirus detection was performed with a mixture of three pairs of oligonucleotide primers: one pair of published primers for amplifying all known enterovirus genomes and two new primer pairs specific for detection of the VP1 genes of HEV71 and CVA16. Enterovirus isolates, CVA16 and HEV71 strains identified previously from patients with HFMD were examined to evaluate the sensitivity and specificity of the multiplex RT-PCR assay. The assay was then applied to the direct detection of these viruses in clinical specimens obtained from HFMD cases identified at Children’s Hospital Number 2, Ho Chi Minh City, Vietnam. The multiplex RT-PCR assay showed 100% specificity in screening for enteroviruses and in identifying HEV71 and CVA16. Similar results were obtained when using the multiplex RT-PCR assay to screen for enteroviruses and to identify HEV71 and CVA16 in clinical specimens obtained from HFMD cases identified at the hospital. This multiplex RT-PCR assay is a rapid, sensitive and specific assay for the diagnosis of HEV71 or CVA16 infection in cases of HFMD and is also potentially useful for molecular epidemiological investigations.